PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 022 SINTONG - Nurjanah '; Sumarno '; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem this research is the students achievement of social studies IV SD N 022 Sintong fourth graderes still low with an average value of 58.00 and minimum completenness criteria (KKM) social studiesis 70. Between students, amounting to 20 people only 8 students who achieve classical KKM with 40%. This research is classroom action research (CAR), which aims to improve the student achievement of social studies class IV at SD N 022 Sintong with implementation cooperative learning model type Berkirim Salam . Formulation of the problem : is the implementation of cooperative learning model type Berkirim Salam can improve students achievement of social studies at SD N 022 Sintong. The research was conducted on February 2, 2016 ‘to February 18, 2016 by 2 cycles. Subjects werw students of SD N 022 Sintong, totaling 20 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 58.00. In the first cycle improve an average of 75.50 and an improve in the second with an average 82.50. Activities of the teacher in the learning process in cycle of 66.67% and the second meeting improve to 77.78%. In the third cycle of the first meeting and the second meeting improve.Keywords: cooperative learning model type Berkirim Salam and improve students and Economic